O desempenho de bilíngues e multilíngues em tarefas de controle inibitório e compreensão auditiva - Limberger, Bernardo Kolling (2014)
Learning and using two or more languages are experiences that impact linguistic and cognitive functioning. Bilingual and multilingual speakers must select the language to be used and, at the same time, suppress the interference of the language not being used. It has been shown that bilinguals/multilinguals have superior performance compared to monolinguals in tasks that tap into executive functioning, due the joint activation of the languages. In case of tasks with linguistic stimuli, the studies are scarce, and the results are less consensual. In the Brazilian context, the effects of bilingualism have not been always found, especially in the speakers of the variety of the German language called Hunsrückisch. Therefore, the goal of this study is to investigate the performance of speakers of Hunsrückisch, bilinguals and multilinguals (the multilinguals learned standard German as well), compared to monolinguals in two tasks. The first task was nonlinguistic, the Attentional Network Task (ANT), and the second was a linguistic task, the Sentence Comprehension Task (TCF), in which the participants listen to canonical sentences (active voice) and noncanonical ones (passive voice), in two languages with or without interference of another sentence. Fifty-nine participants were divided in three groups: monolinguals, bilinguals and multilinguals, consisting of adults (mean age = 28.9 years); these participants were mainly from the city of São José do Hortêncio (RS). The participants completed a questionnaire about linguistic and cognitive issues, made a working memory task and the above tasks. With statistical tests, we analyzed the dependent variables response time and accuracy in the two tasks. The results showed that there are no differences between the groups on the accuracy of the ANT. The difference happened on the time it took to respond: multilinguals were faster than monolinguals on all experimental conditions. Bilinguals were faster too, but the difference was not significant. In another task, the TCF, the monolinguals had better overall accuracy. All groups were more accurate and faster in comprehension of canonical sentences in comparison to noncanonical ones, and in comprehension without interference in comparison to comprehension with interference. There were no differences between the groups on the global response times. The results show that multilinguals have an advantage in comparison to monolinguals on the executive processing with nonlinguistic stimuli. It seems they have a more developed ability of the multilinguals on responding faster in a nonlinguistic task, that involves the executive functions, and not necessarily only on the inhibitory control. When the task has linguistic stimuli, the results are not so uniform. In this study, we found that in the Brazilian context of minority languages, especially the multilingualism can provide positive effects on the cognition, especially in the global response times.